It takes two: An antenatal to postnatal RDoC framework for investigating the origins of maternal attachment and mother–infant social communication. (December 2021) - DiPietro, Janet A.; Kivlighan, Katie T.; Voegtline, Kristin M.; Costigan, Kathleen A.; Moore, Ginger A.
Abstract: Transformation of the maternal–fetal relationship into the mother–infant relationship remains an enigmatic process. This progression is considered using a Research Domain Criteria (RDoC) informed approach centered on domains of Arousal/Regulation, Positive/Negative Valence, and Social Processes. One hundred and fifty-eight maternal–fetal dyads began participation during pregnancy, maternal–infant dyads were followed at 6 months postpartum. Women exhibited stability in feelings of attachment to the fetus and infant, and in positive/negative appraisal of pregnancy and motherhood. Elicited maternal physiological arousal to emotionally evocative videos generated fetal heart rate variability and motor activity responses. Parasympathetic (i.e., heart rate variability) suppression in the fetus was associated with more positive and regulated infant social communication in the Face-to-Face Still Face protocol; suppression of maternal respiratory sinus arrhythmia was related to infant affect but in the opposite direction. Maternal ratings of infant temperament aligned with maternal antenatal affective valence. Attachment trajectories characterized by stability from antenatal to postnatal periods were most associated with maternal affective appraisal of pregnancy; shifts were influenced by infant characteristics and maternal sympathetic responsivity. Results illustrate how variation in arousal and regulatory systems of the pregnant woman and fetus operate within the context of maternal positive and negative valence systems to separately and jointly shape affiliation and temperament in early infancy.